A Novel Study of Methane-Rich Gas Reforming to Syngas and Its Kinetics over Semicoke Catalyst - Guojie Zhang; Aiting Su; Jiangwen Qu; Yannian Du (The Scientific World Journal)
A small-size gasification unit is improved through process optimization to simulate industrial United Gas Improvement Company gasification. It finds that the reaction temperature has important impacts on semicoke catalyzed methane gas mixture. The addition of water vapor can enhance the catalytic activity of reforming, which is due to the fact that addition of water vapor not only removes carbon deposit produced in the reforming and gasification reaction processes, but also participates in gasification reaction with semicoke to generate some active oxygen-containing functional groups. The active oxygen-containing functional groups provide active sites for carbon dioxide reforming of methane, promoting the reforming reaction. It also finds that the addition of different proportions of methane-rich gas can yield synthesis gas with different H2/CO ratio. The kinetics study shows that the semicoke can reduce the activation energy of the reforming reaction and promote the occurrence of the reforming reaction. The kinetics model of methane reforming under the conditions of steam gasification over semicoke is as follows: k-=5.02×103·pCH40.71·pH20.26·exp(−74200/RT).